CSF levels of the neuronal injury biomarker visinin‐like protein‐1 in Alzheimer's disease and dementia with Lewy bodies. (26th June 2013) - Luo, Xinni; Hou, Le; Shi, Haishan; Zhong, Xiaomei; Zhang, Yufeng; Zheng, Dong; Tan, Yan; Hu, Guoyan; Mu, Nan; Chan, Jianping; Chen, Xinru; Fang, Yaxiu; et al.
Abstract The overlapping clinical features of Alzheimer's disease (AD) and Dementia with Lewy bodies (DLB) make differentiation difficult in the clinical environment. Evaluating the CSF levels of biomarkers in AD and DLB patients could facilitate clinical diagnosis. CSF Visinin‐like protein‐1 (VILIP‐1), a calcium‐mediated neuronal injury biomarker, has been described as a novel biomarker for AD. The aim of this study was to investigate the diagnostic utility of CSF VILIP‐1 and VILIP‐1/Aβ1–42 ratio to distinguish AD from DLB. Levels of CSF VILIP‐1, t‐tau, p‐tau181P, Aβ1–42, and α‐synuclein were measured in 61 AD patients, 32 DLB patients, and 40 normal controls using commercial ELISA kits. The results showed that the CSF VILIP‐1 level had significantly increased in AD patients compared with both normal controls and DLB patients. The CSF VILIP‐1 and VILIP‐1/Aβ1–42 levels had enough diagnostic accuracy to allow the detection and differential diagnosis of AD. Additionally, CSF VILIP‐1 levels were positively correlated with t‐tau and p‐tau181P within each group and with α‐synuclein in the AD and control groups. We conclude that CSF VILIP‐1 could be a diagnostic marker for AD, differentiating it from DLB. The analysis of biomarkers, representing different neuropathologies, is an important approach reflecting the heterogeneous features of AD and DLB. <boxed-text content-type="graphic" id="jnc12331-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text> Neuronal Ca2+‐sensor protein VILIP‐1 has been implicated in the calcium‐mediated neuronal injury and pathological change of AD. The CSF VILIP‐1 and VILIP‐1/Aβ1‐42 levels had enough diagnostic accuracy to allow the detection and differential diagnosis of AD. CSF VILIP‐1 is a useful biomarker for AD. Evaluating the CSF levels of VILIP‐1 in AD and DLB patients could facilitate clinical diagnosis.